A língua na tela: descrição e análise da variação do objeto direto anafórico de terceira pessoa em legendas profissionais e fansubs - Azevedo, Lívia Oliveira (2024)
Assuming that an examination of the intersections between linguistic variation and genres is not only desirable but essential to understand variation (Vieira; Lima, 2019; Biazolli; Berlinck, 2021; Lima, 2022; Vieira, in progress), this study aims to (i) discuss how the realization of third-person anaphoric direct object occurs in a corpus of subtitles for the TV show Grey’s Anatomy and (ii) describe audiovisual subtitles as a genre. Based on the theoretical and methodological framework of the Theory of Variation and Linguistic Change (Weinreich; Labov; Herzog, 2006[1978]; Labov, 1982, 2001, 2003, 2008[1972]), the first step of the research was the compilation of the corpus of subtitles, which gathered two samples: one of professional subtitles extracted from the Amazon Prime Video streaming platform using a user script, and another of fan-made subtitles downloaded for free from the Legendas.TV website – the so-called fansubs. With this material, the characterization of the subtitles based on the concept of genre (Bakhtin, 2016[1979]; Marcuschi, 2005, 2008, 2010) began, considering structural characteristics discussed through the principles of Audiovisual Translation (Zabalbeascoa, 2008; Díaz-Cintas, 2010; Remael, 2010; Franco; Araújo, 2011), and situational characteristics, based on the proposal of Biber and Conrad (2009). Simultaneously, all occurrences of the phenomenon were collected, and the independent variables of the study were defined, considering both the literature on the phenomenon available (cf. Omena, 1978; Duarte; 1986; Cyrino, 1994; Marafoni, 2004; Freire, 2005; Santana, 2016; Lima, 2022, among others), and the specificities of the genre at focus. After each occurrence was encoded, the statistical analysis of the data was conducted using the R platform (R Core Team, 2023). As a general result, a prevalence of the accusative clitic was observed in the corpus, with this being the most used variant in all contexts, except in two: when referring to antecedents that were not animated and as complements of non-finite forms, both of which had the null object as the most productive strategy. The phenomenon was correlated not only to linguistic but also to extralinguistic variables, including genre-related ones such as number of characters per line and per second. Combining the results of the statistical analyses with a qualitative examination focused on the subtitles, it was concluded that the analyzed samples seem to be quite homogeneous, with little difference between professional subtitles and fansubs, which suggests that the different production contexts of these two types of subtitles do not have a relevant impact on the linguistic uses observed. Furthermore, the realization of the third-person anaphoric accusative seemed to occur in a particular way in subtitles, presenting strong connection with the structural and situational specificities of this genre.